Development of a Physiologically Based Pharmacokinetic Model of Mitragynine, Psychoactive Alkaloid in Kratom (Mitragyna Speciosa Korth.), In Rats and Humans - Kimheang Ya (2022)
Mitragynine is a major psychoactive alkaloid in leaves of kratom (Mitragyna speciosa Korth.). To understand its disposition in organs, this study aimed to develop a physiologically based pharmacokinetic (PBPK) model that predicts mitragynine concentrations in plasma and organ of interests in rats and humans. The PBPK model consisted of six organ compartments (i.e. lung, brain, liver, fat, slowly perfused tissues, and rapidly perfused tissue). From systematic searching, three pharmacokinetic studies of mitragynine (two studies in rats and 1 study in humans) were retrieved from the literature. Berkeley Madonna Software (version 8.3.18) was used for model development and model simulation. The developed PBPK model consisted of biologically relevant features following involvement of (i) breast cancer-resistant protein (BCRP) in brain, (ii) a hepatic cytochrome P450 3A4 (CYP3A4)-mediated metabolism in the liver, and (iii) a diffusion-limited transport in fat. The simulations adequately describe simulated and observed data in the two species with different dosing regimens. PBPK models of mitragynine in rats and humans were successfully developed. The models may be used to guide optimal mitragynine dosing regimens.